Quality of dried apple products added with active compounds - Cortés R., Misael; Chiralt B., Amparo; Arango T, Julio C. (Revista de Ciencias Agrícolas, 2016)
The aim of this research was to assess the quality attributes of air dried and lyophilized apples previous a pretreatment of vacuum impregnation (VI) with vitamin E. The air drying process (ADP) was carried out in a tray dryer at 40ºC, relative humidity of 59±7% and air speed of 0.7m/s. The lyophilization process (LP) was in turn conducted with a vacuum pressure of 1.2 x 10-3 kPa, condenser’s temperature of -45ºC, and the tray’s temperature of 25ºC. The vitamin E was quantified using gas chromatography with a flame ionization detector on the extracts of hexane samples. Apples ADP and LP had 0.72 ± 0.12 and 1.34 ± 0.14 mg dl-α-tocopherol acetate/g; 12.6±1.7 and 7.9±2.0 % moisture, respectively. Products resulting from ADP showed browning, whereas those resulting from LP were lighter in color (>L*), greenish (>a*), less yellow (<b*) and less saturated (<Cab*). Products obtained through LP had a crunchy texture, while those obtained by ADP were rubbery. The integrated processes VI+ADP or VI+LP do not cause a significant alteration of the vitamin E. Therefore, this is a good procedure for extending the shelf life of products without decreasing their nutritional characteristics.